The poverty of postmodernism - O'Neill, John, 1933 (London ; New York : Routledge, 1995)
In this book John O'Neill examines the postmodern turn in the social sciences. He rejects the current celebration of knowledge and value relativism on the grounds that it renders critical reason and common sense incapable of resisting the superficial ideologies of minoritarianism that leave the hard core of global capitalism unanalysed. From a phenomenological standpoint (Husserl, Merleau-Ponty, Schutz, Winch), O'Neill challenges Lyotard's post-traditionalist reading of Wittgenstein and Habermas in order to defend commonsense reason and values that are constitutive of the everyday life-world. In addition he argues from the standpoint of Vico and Marx on the civil history of embodied mind that the post-rationalist celebration of the arts of superficiality undermines the recognition of the cultural debt each generation owes to past and post-generations.
In a positive way O'Neill develops an account of the historical vocation of reason and of the charitable accountability of science to commonsense that is necessary to sustain the basic institutions of civic democracy. This book will be of interest to anyone concerned to understand the continuing relevance of Marx, Weber, Husserl and Schutz to the debates around Wittgenstein, Lyotard, Foucault and Jameson.
Includes bibliographical references and index.
Keywords: Postmodernism -- Social aspects